Environmental economic an elementary introduction - Kerry Turner, R | Pearce, David | Bateman, Ian (University Press / Baltimore, 1993)
The subject of environmental economics has became on important focus of debate around the world, with experts as well as ordinary citizens concluding that the environmental and the economy